Eucalyptus expansion in Brazil: Energy yield in new forest frontiers. (January 2021) - Cunha, Thammi Queuri Gomes da; Santos, Alyne Chaveiro; Novaes, Evandro; Hansted, Ana Larissa Santiago; Yamaji, Fabio Minoru; Sette Jr, Carlos Roberto
Abstract: An expansion of planted Eucalyptus spp. forests can supply an important part of society's demand for biofuels. To do so, a diversity of genetic materials field-grown under seasonal drought stress, different soil type and technological wood qualities have to be evaluated in new forest frontiers. The aim of this study was to evaluate the yield and wood characteristics of five Eucalyptus spp. clones in a field experiment with regard to E. urophylla x E. grandis, E. resinifera x E. grandis, E. pellita x E. grandis, E. urophylla x E. camaldulensis, and E. urophylla species/hybrids at three sites in the Midwest region of Brazil, considered a new forest frontier in the country. The experiments were installed in the cities of Catalão, Luziânia, and Corumbá, Goiás state, Brazil. The mean annual increment (MAI) was calculated, trees were cut and wood samples were obtained five years after installing the experiment to determine the wood basic density, higher heating value, energy density, dry mass, and energy yield. The energy yield and wood characteristics of Eucalyptus spp. were influenced by genotype (clone), environment (site), and interaction (genotype x environment) at different intensity levels. The clone with E. camaldulensis genes presented good performance (MAI) under adverse conditions (Corumbá) and the wood basic density of this clone may be less affected by environmental variations when compared to the other clones and species/hybrids evaluated in this study. The C1 clone ( E. urophylla x E. grandis ) was the most suitable for large-scale forest implantation in the Corumbá region. The C2 clone ( E. resinifera x E. grandis ) results showed it to be the most suitable for Catalão, while the best clones for Luziânia were C1 and C2. This study can be used as an indication for choosing the best eucalyptus for new areas (new forest frontiers) with similar edaphoclimatic conditions. Highlights: Eucalyptus spp. clones field-grown under seasonal drought stress and different soil type were evaluated. Energy yield and wood characteristics of Eucalyptus spp. were influenced by genotype, environment, and interaction. This study can be used as an indication for choosing the best eucalyptus for new areas with similar edaphoclimatic conditions.